2004
DOI: 10.1016/j.ejcnurse.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomena of Participation and Non-Participation in Health Care-Experiences of Patients Attending a Nurse-Led Clinic for Chronic Heart Failure

Abstract: The study suggests an extended view on the concept of participation. Patients' experiences of participation in health care can vary and should therefore be an issue for dialogue between nurses and patients with CHF in nurse-led specialist clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
2
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(183 citation statements)
references
References 35 publications
9
159
2
13
Order By: Relevance
“…Se debe tener en cuenta, sin embargo, que generalmente el nivel de respeto de derechos de usuarios es menor en servicios psiquiátricos de hospitalización que en los ambulatorios 12,22 . En países de Europa Occidental se han realizado varios estudios de servicios ambulatorios de Psiquiatría y de otras especialidades, utilizando métodos diferentes al QualityRights, en los que se han medido el respeto de algunos de los derechos evaluados en nuestra investigación, tales como consentimiento informado, trato adecuado a los usuarios, consideración de las preferencias de los usuarios, apoyo para la inclusión social, acceso a la ficha clínica y confidencialidad [22][23][24][25][26][27][28][29] . En estos estudios se aprecia que los procedimientos desarrollados y el nivel de resguardo y ejercicio de derechos son superiores a los resultados encontrados en los servicios de Psiquiatría Ambulatoria chilenos.…”
Section: Discussionunclassified
“…Se debe tener en cuenta, sin embargo, que generalmente el nivel de respeto de derechos de usuarios es menor en servicios psiquiátricos de hospitalización que en los ambulatorios 12,22 . En países de Europa Occidental se han realizado varios estudios de servicios ambulatorios de Psiquiatría y de otras especialidades, utilizando métodos diferentes al QualityRights, en los que se han medido el respeto de algunos de los derechos evaluados en nuestra investigación, tales como consentimiento informado, trato adecuado a los usuarios, consideración de las preferencias de los usuarios, apoyo para la inclusión social, acceso a la ficha clínica y confidencialidad [22][23][24][25][26][27][28][29] . En estos estudios se aprecia que los procedimientos desarrollados y el nivel de resguardo y ejercicio de derechos son superiores a los resultados encontrados en los servicios de Psiquiatría Ambulatoria chilenos.…”
Section: Discussionunclassified
“…When the nurse merely delivered information about MI and lifestyle changes without involving the patient as the owner of the problem, it was hard to find motivation for lifestyle changes. Eldh et al [28] describes the patient's non-participation as arising from a feeling of not being in control of the situation, and that your opinion does not even count. In an extensive concept analysis on health assets, Rotegård et al [29] identified motivational strength as an important asset for lifestyle changes.…”
Section: Critical Interpretation and Reflectionsmentioning
confidence: 99%
“…Because patients with CHF want to participate actively in discussions about their care and treatment, it is extremely important that health professionals encourage such participation 12 . Although we have recently shown that highly adherent patients have better clinical outcomes, pedagogical strategies to obtain good information about medicines remain a challenge.…”
Section: Article P 737mentioning
confidence: 99%